Dual mechanism for inhibition of inwardly rectifying Kir2.x shannels by quinidine involving direct pore block and PIP2-interference - Köpple, Christoph; Scherer, Daniel; Seyler, Claudia; Scholz, Eberhard P.; Thomas, Dierk; Katus, Hugo; Zitron, Edgar (The journal of pharmacology and experimental therapeutics, 2017)
Class IA antiarrhythmic drug quinidine was one of the first clinically used compounds to terminate atrial fibrillation and acts as multichannel inhibitor with well-documented inhibitory effects on several cardiac potassium channels. In the mammalian heart, heteromeric assembly of Kir2.1-2.3 channels underlies IK1 current. Although a low-affinity block of quinidine on Kir2.1 has already been described, a comparative analysis of effects on other Kir2.x channels has not been performed to date. Therefore, we analyzed the effects of quinidine on wild-type and mutant Kir2.x channels in the Xenopus oocyte expression system. Quinidine exerted differential inhibitory effects on Kir2.x channels with the highest affinity toward Kir2.3 subunits. Onset of block was slow and solely reversible in Kir2.2 subunits. Quinidine inhibited Kir2.x currents in a voltage-independent manner. By means of comparative Ala-scanning mutagenesis, we further found that residues E224, F254, D259, and E299 are essential for quinidine block in Kir2.1 subunits. Analogously, quinidine mediated Kir2.3 inhibition by binding corresponding residues E216, D247, D251, and E291. In contrast, Kir2.2 current block merely involved corresponding residue D260. Using channel mutants with altered (phosphatidylinositol 4,5-bisphosphate PIP2) affinities, we were able to demonstrate that high PIP2 affinities (i.e., Kir2.3 I214L) correlate with low quinidine sensitivity. Inversely, mutant channels interacting only weakly with PIP2 (i.e., Kir2.1 K182Q, and L221I) are prone to a higher inhibitory effect. Thus, we conclude that inhibition of Kir2.x channels by quinidine is mediated by joint modes of action involving direct cytoplasmic pore block and an impaired channel stabilization via interference with PIP2.